Lactation Plays a Fundamental Role in Developmental Programming - Ramirez, Victoria; Montaño, Francisco A.; Bautista, Regina J.; Mummidi, Srinivas; Alvarenga, Juan C.; Bautista, Claudia J. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Breast milk has been considered the best source of nutrition for newborns. Several epidemiological and basic experimental studies have been conducted to understand the nutritional advantages of breast milk. Previous findings have emphasized the importance of good maternal nutrition. Maternal milk provides macromolecules, minerals, immune cells, antibodies, hormones, and regular flora to strengthen their offspring preventing various diseases. Maternal milk helps to facilitate physiological, and molecular maturation of several systems, which are important for the final maturation of organs and newborn body development. Currently, breastfeeding is being abandoned for various reasons, such as lower milk production, lack of time, abandonment of the family, social or emotional problems and adverse environmental conditions. These permanent alterations during a critical developmental window have negative consequences in regard to the development of the offspring and organ maturation leading to metabolic, reproductive, hormonal and physiological problems from early life to adulthood. This review describes the advantages of breast milk and the importance for the mother to maintain an adequate diet during pregnancy and lactation, in addition to maintaining a healthy lifestyle and harmonious family relationships. Such an environment will contribute to the complete maturation and development of the offspring.
Keywords: milk benefits